Odnos prebivalstva slovenskih alpskih turističnih krajev do turizma in njegovih učinkov - Cigale, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
The aim of this paper was to find out how the local inhabitants perceive positive and negative tourism impacts in Slovenian alpine areas and how this perception influence their attitude toward tourism. A questionnaire survey was undertaken in five different tourist resorts. Despite the differences between resorts there are many similarities in perception of tourism impacts. In all cases positive attitudes toward tourism prevail. In general the economic impacts were perceived as the most important and the socio-cultural impacts as the least important.
Keywords: Alpe; Alps; geografija; geography; Slovenia; Slovenija; sonaravni razvoj; sustainable development; tourism; trajnostni razvoj; turizem; učinki